Alcohol consumption, cigarette smoking, and risk of breast cancer for BRCA1 and BRCA2 mutation carriers: results from The BRCA1 and BRCA2 Cohort Consortium - Li, Hongyan; Terry, Mary Beth; Antoniou, Antonis C.; Phillips, Kelly-Anne; Kast, Karin; Mooij, Thea M.; Engel, Christoph; Noguès, Catherine; Stoppa-Lyonnet, Dominique; Lasset, Christine; Berthet, Pascaline; Mari, Veronique; et al. (Cancer epidemiology, biomarkers & prevention : a publication of the American Association for Cancer Research, cosponsored by the American Society of Preventive Oncology, 2020)
BACKGROUND Tobacco smoking and alcohol consumption have been intensively studied in the general population to assess their effects on the risk of breast cancer (BC), but very few studies have examined these effects in BRCA1 and BRCA2 mutation carriers. Given the high BC risk for mutation carriers and the importance of BRCA1 and BRCA2 in DNA repair, better evidence on the associations of these lifestyle factors with BC risk is essential. METHODS Using a large international pooled cohort of BRCA1 and BRCA2 mutation carriers, we conducted retrospective (5,707 BRCA1 mutation carriers; 3,525 BRCA2 mutation carriers) and prospective (2,276 BRCA1 mutation carriers; 1,610 BRCA2 mutation carriers) analyses of alcohol and tobacco consumption using Cox proportional hazards models. RESULTS For both BRCA1 and BRCA2 mutation carriers, none of the smoking-related variables was associated with BC risk, except smoking for more than five years before a first full-term pregnancy (FFTP) when compared to parous women who never smoked. For BRCA1 mutation carriers, the HR from retrospective analysis (HRR) was 1.19 (95%CI:1.02,1.39) and the HR from prospective analysis (HRP) was 1.36 (95%CI:0.99,1.87). For BRCA2 mutation carriers, smoking for more than five years before a FFTP showed an association of a similar magnitude, but the confidence limits were wider (HRR=1.25,95%CI:1.01,1.55 and HRP=1.30,95%CI:0.83,2.01). For both carrier groups, alcohol consumption was not associated with BC risk. CONCLUSIONS The finding that smoking during the pre-reproductive years increases BC risk for mutation carriers warrants further investigation. IMPACT This is the largest prospective study of BRCA mutation carriers to assess these important risk factors.